DETERMINANT OF RICE PRICE IN INDONESIA: A FOURIER ENGLE-GRANGER COINTEGRATION TEST - Ariani, Rita; Nurjannah, Nurjannah; Adhiana, Adhiana; Fachrurrozi, Kamal (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The issue of food prices is a critical topic that need to be discussed. Food prices has implications on economic and society. In Indonesia, rice is the most widely comsumed staple. Unfortunately, the prices of rice are often unstable due various factors. This research investigates the relationship between exchange rate, money supply, and volatility of oil prices on rice prices in Indonesia.The research study used data from the period February 2008 to December 2022 based on data availability. All research data used are secondary data with time series type. Rice price data is sourced from the Food and Agriculture Organization (FAO), exchange rates and oil prices are sourced from the Federal Reserve Economic Data (FRED), and money supply is sourced from the Indonesia Economic and Financial Statistics (SEKI). This study uses the Fourier Engle-Granger (FEG) cointegration method as a novelty in looking at cointegration that has structural breaks and the FMOLS, DOLS, and CCR methods as analysis. The results found that the research variables were found to have cointegration in the rice price model. Furthermore, the exchange rate was found to have a significant negative effect (-0.454%, -0.420%, -0.456%) on rice prices. The money supply had a significant positive effect (0.640%, 0.627%, 0.639%), and the volatility of oil prices had a significant positive effect (0.024%, 0.031%, 0.026%) on rice prices. The results of this research have important policy implications for policymakers to control money circulation, maintain exchange rate stability, and use renewable energy alternatives.